Renaissance Polish Steel Industry - Wieloński, Andrzej (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2009)
In 2006 Poland’s steel makers produced steel makers produced about 10 M mt crude steel (in 2002 - 8,4 M mt); consumption in 2006 was 10,7 m mt (in 2002 - 7,1 M mt). Flat products prevailed within domestic consumption of steel (51% of total consumption). Imports to consumption were 50%. Higher steel consumption was mainly driven by Polish economy growing fast, absorption of EU structural funds into growth0boosting and new projects.